Quercetin: Prooxidant Effect and Apoptosis in Cancer - Mateus, Paola G. [UNESP]; Wolf, Vanessa G. [UNESP]; Borges, Maiara S. [UNESP]; Ximenes, Valdecir F. [UNESP] (Elsevier, 2018)
Quercetin is the main flavonoid present in the human diet, being the most characteristic representative of the subclass flavonols. Although the beneficial health effects of quercetin are usually linked to its antioxidant properties, there is substantial evidence that its prooxidant features are also relevant regarding its tumoricidal effects. Here we aim to demonstrate that the generation of reactive oxygen species (ROS) by quercetin could also be a desired biological property. The oxygen paradox and its relationship with the mechanisms of intracellular generation of ROS and autoxidation of polyphenols are described herein. The chemical properties, susceptibility to autoxidation, and the role of quercetin as a cocatalyst in peroxidase-mediated reactions are also discussed. The signaling pathways related to apoptosis and their relationship with intracellular redox imbalance are presented. Oxidation therapy, a strategy to treat cancer, and its relationship with ROS and apoptosis are also discussed in the chapter. Finally, we present several experimental findings that support the proposal that the capacity of quercetin as a phytochemical that is able to trigger apoptosis in several tumor cell lineages might be related to its prooxidant features. In conclusion, we propose that quercetin should be considered as a redox-active compound, that, by altering the cellular redox status, through anti- or prooxidant action, is able to promote tumoricidal effects.
Keywords: Apoptosis; Autoxidation; Cancer; Oxidation therapy; Prooxidant; Quercetin